Sustainable Water Solutions: Solar- Driven Distillation and Real-Time Monitoring for Rural Community - Annis Farhana Raymedin; Fathullah Mohammed Fathullah Alqamoudi; Khasyfee Ihtifazhuddin Jasmee; Muhammad Aliff Hafeez Azman; Nurfaraliyana Samburi; Mahyuzie Jenal (Journal of Electronic Voltage and Application, 2024)
In an era characterized by rapid population growth and urban sprawl, access to clean water has become a significant concern for societies around the globe. As the world’s most precious resource, water scarcity poses a significant challenge to the sustainability of our planet’s ecosystems, economies, and human health. However, despite this issue of modernity, the demand for clean water in rural areas is more pressing and must be taken seriously in order to involve the demands of relevant and up to date processes. Therefore, in-depth studies to maintain quality water for this concern area have become increasingly popular and received the attention of many parties. Thus, the seawater distillation method powered by solar panels has been identified as the most effective technological alternative, accessible source of supply and is able to produce more consistent results. The specific methodology implemented involves several components and processes such as 12V solar panels, batteries, inverters, heating coils, water pumps, charging controllers, microcontrollers, sensors, liquid crystal displays and 2-channel relay modules. Next the target for this work is that the evaporation process will take place and the condensing unit will store the distilled water in a specified container. Subsequently, observe the results of the experiment by measuring the water level at different times and finally it is expected that the water level will increase as the hours increase.